2017
DOI: 10.3389/fphar.2017.00493
|View full text |Cite
|
Sign up to set email alerts
|

Establishment and Characterization of a Novel Rat Model of Mechanical Low Back Pain Using Behavioral, Pharmacologic and Histologic Methods

Abstract: Chronic low back pain (LBP), the leading cause of disability globally, is notoriously difficult to treat. Most rodent models of LBP mimic lumbar radicular pain rather than mechanical LBP. Here, we describe establishment of a new rat model of mechanical LBP that is devoid of a neuropathic component. Groups of adult male Sprague Dawley rats were anesthetized and their lumbar L4/L5 and L5/L6 intervertebral disks (IVDs) were punctured (0.5 mm outer diameter, 2mm-deep) 5 (LPB-5X), or 10 (LBP-10X) times per disk. Sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(39 citation statements)
references
References 55 publications
7
32
0
Order By: Relevance
“…Two-way ANOVA and Tukey's multiple comparison test were used for statistical analysis). [9,15]. Moreover, SP and CGRP, direct pain-related peptides, acted as the "biomarkers" of pain, which was in accordance with behavioral assessment, further validating LBP in rodents.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Two-way ANOVA and Tukey's multiple comparison test were used for statistical analysis). [9,15]. Moreover, SP and CGRP, direct pain-related peptides, acted as the "biomarkers" of pain, which was in accordance with behavioral assessment, further validating LBP in rodents.…”
Section: Discussionsupporting
confidence: 61%
“…Here, the IVDs at L4~5 and L5~6 were punctured with an 18-gauge needle based on a previous report to establish the LBP model [15]. The puncture would directly alter the mechanical properties of the IVDs, thus causing damage to the annulus fibrosus and an increase in cytokines [16], which finally caused IVD degeneration and discogenic LBP [10].…”
Section: Discussionmentioning
confidence: 99%
“…Based on the animal ethics principle of “Reduction,” a “washout protocol” was used such that each rat received up to a maximum of four individual intraperitoneal (i.p.) doses of J-2156 or vehicle with at least 2–3 days of “washout” between successive doses as per the common practice in pain research (Zeppetella et al, 2003 ; Kim et al, 2010 ; Otto et al, 2011 ; Varamini et al, 2012 ; Muralidharan et al, 2013 , 2017 ; Han et al, 2014 ; Khan et al, 2014 ; Otis et al, 2016 ; Friton et al, 2017a , b ; Shenoy et al, 2017 ; Suzuki et al, 2017 ). The animals that received a new treatment on a different occasion after the washout period, were cumulatively added to build the “n” numbers.…”
Section: Methodsmentioning
confidence: 99%
“…All other graphs were stored, represented and analyzed using the GraphPad Prism TM (v7.00) software. The ED50 values were calculated as per the method described previously (Rowlett et al, 1999 ; Muralidharan et al, 2013 , 2017 ; Han et al, 2014 ; Khan et al, 2014 ; Shenoy et al, 2017 ). The change in the PWT values (ΔPWT) in the hindpaws of rats following administration of single bolus doses of J-2156 or vehicle was determined by subtracting the predosing PWT values from the respective post-dosing PWT values for individual rats at each time-point i.e.,…”
Section: Methodsmentioning
confidence: 99%
“…However, its efficacy in a mild to moderate rat model of chronic mechanical LBP remains to be assessed. Hence, the aims of our research herein were (a) to assess the face validity of our previously reported LBP‐5X rat model of mild to moderate cLBP 16 using clinically available analgesic/adjuvant agents and, (b) to assess the anti‐hyperalgesic efficacy of single bolus doses of J‐2156 in our LBP‐5X rat model of mild to moderate chronic mechanical LBP.…”
Section: Introductionmentioning
confidence: 99%